Globalization and the meaning of Canadian life - Watson, William G. (Toronto ; Buffalo : University of Toronto Press, 1998)
"Globalization - seemingly the dominant economic force of this era - is a phenomenon that invites misrepresentation and exaggeration. One of its results has been to introduce several false premises into the country's policy debates. So says William Watson, whose new book draws on economics and history to pose interesting challenges to modes of thinking that have become habitual in late twentieth-century Canadian life."--Jacket
pt. 1. Globalization. 1. Defining Moment. 2. The Globalization Hypothesis. 3. Four Hundred Years of Globalization. 4. Convergence? 5. Home Truths. 6. Are We There Yet? 7. Free to Choose -- pt. II. The Meaning of Canadian Life. 8. False Premise. 9. Governing Misperceptions. 10. The American 'Governmental Habit'. 11. T̀he Most Rugged Surviving Individualists'. 12. The American Lead. 13. Canadian Free Enterprise. 14. The Unimportance of Being Different. 15. Distinct Society? 16. Cement for a Nation? 17. The Rising Cost of Civilization. 18. The Psychic Costs of Government. 19. Virtually Canadian. 20. Do Countries Still Make Sense?
Includes bibliographical references (pages 289-303) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Canada -- Civilization -- 1945- -- Foreign influences; Canada -- Foreign economic relations; Globalization; Canada -- Civilization -- 1945-; International economic integration; Canada -- Civilization -- Foreign influences; Canada -- Civilisation -- Influence étrangère.; Canada -- Civilisation -- 1945-; Canada -- Relations économiques extérieures.; Intégration économique internationale; Canada -- Civilisation -- 1945- -- Influence étrangère.; Mondialisation; globalism; HISTORY -- Canada -- General; POLITICAL SCIENCE -- Globalization; International economic integration; Civilization; Civilization -- Foreign influences; Globalization; International economic relations; Canada; Kanada; Auslandsbeziehungen; Kultur; Wirtschaft; Government size; Globalisierung; Wirtschaftsintegration; Welt; Kanada; Staatsquote; Regierung; Finanzpolitik; Nation; Since 1945